KONSEP SAKINAH MAWADDAH WARRAHMAH MENURUT ISLAM - Dwi Runjani Juwita (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2017)
One of the words that is often spoken for a relationship in the household is sakinah mawaddah warrahmah (samara). The family sakinah mawaddah warrahmah is a family that is coveted by every married couple. The term samara is a prayer that is often offered and expected by Muslims who have married and fostered the family. In the Qur'an there are several verses that mention the words sakinah mawaddah warrahmah. This shows that Islam also discusses the concept of a happy family that is sakinah mawaddah warrahmah. The samara family is certainly not just a slogan in the teachings of Islam. This is the goal of the family in Islam. Then how the principles or characteristics in the family sakinah mawaddah warrahmah are?